2015
DOI: 10.1007/s00167-015-3834-y
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term outcomes of mosaicplasty versus arthroscopic microfracture with or without platelet-rich plasma in the treatment of osteochondral lesions of the talus

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 25 publications
1
73
2
Order By: Relevance
“…[9][10][11][12]7 Guney and colleagues also report in their study that mosaicplasty reduces the pain of affected individuals more than arthroscopic microfracture and this result can be due to the quality of the hyaline cartilage formed with the former strategy. 9 Almost can be said that the mosaicplasty is a reliable method for reducing symptoms under the conditions of Osteochondral lesions of the ankle joint. Some studies have acknowledged that the subchondral bone has an important role as a pain source that heals in this treatment.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[9][10][11][12]7 Guney and colleagues also report in their study that mosaicplasty reduces the pain of affected individuals more than arthroscopic microfracture and this result can be due to the quality of the hyaline cartilage formed with the former strategy. 9 Almost can be said that the mosaicplasty is a reliable method for reducing symptoms under the conditions of Osteochondral lesions of the ankle joint. Some studies have acknowledged that the subchondral bone has an important role as a pain source that heals in this treatment.…”
Section: Resultsmentioning
confidence: 96%
“…13 Six studies have confirmed the positive effect of mosaicplasty on the functional ability of individuals with Osteochondral lesions of the ankle joint. 7,9,10,12,14,15 34% of the studies presented did not report any benefits. The results of these studies show that these patients with functional limitations will perform better after treatment.…”
Section: Resultsmentioning
confidence: 96%
“…Several methods have been described in the literature for the treatment of OLT. 1,[3][4][5][6][7][8]11,14,15 Different treatment strategies are adopted according to the localization, dimensions and aetiology of the lesion. Successful results have been reported with the use of several different protocols such as nonoperative treatments, arthroscopic drilling and the application of microfracture, fragment excision or curettage, bone grafting or osteochondral transplantation (OCT).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Smyth et al[57] found in a rabbit model, that application of PRP at time of AOT improved the integration of the osteochondral graft at the cartilage interface and decreased graft degeneration. In clinical studies, Guney et al[58] performed a randomized control trial in 19 OLT patients and reported that BMS with PRP had better functional outcomes when compared with BMS alone. Görmeli et al[59] compared the effect of PRP and HA following BMS for OLT and found at 15.3-mo follow-up, clinical improvement after PRP with HA when compared to HA or saline injection alone.…”
Section: Biologic Augumentation For Cartilage Repairmentioning
confidence: 99%